Teachers' Communication Skills in Technology-Based Learning and its Impact on Students' Affective Responses - Farid Zaenudin Asnawi; Umi Sumbulah; Muhammad Amin Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to explore teachers' communication skills in interactive multimedia-based learning and its impact on students' affective responses on Islamic Religious Education (PAI) materials, particularly the Story of the Hijrah of Prophet Muhammad S.A.W. This research was conducted at SDN 05 Merjosari Malang City and SDN Cawang 09 Jakarta, which have started using technology, especially Lectora interactive multimedia software. Using a mixed approach with qualitative dominance, the study combined observations, interviews and questionnaires to measure students' perceptions of teacher credibility and their affective responses. The results showed that the use of Lectora improved teachers' communication from one-way with printed media to more interactive and multimodal. This improvement strengthens teacher credibility, especially in terms of expertise and concern for students. Students' affective responses, such as interest, motivation and emotional engagement, improved significantly, with a 23.4% increase compared to print media. Students' cognitive completion also improved, with 75% of students achieving the Minimum Completion Criteria (MCC), compared to 14.3% in the pre-cycle. This research shows that technology-based learning, particularly interactive media such as Lectora, can improve the quality of learning communication and students' emotional engagement, which supports better understanding of the material. These results provide practical guidance for teachers and educational institutions in designing more effective and meaningful learning.